Taxon-specific evolution of glandular kallikrein genes and identification of a progenitor of prostate-specific antigen. - Olsson, A; Lilja, H; Lundwall, A (2004)
In a previous study we demonstrated that repeated duplications of the tissue kallikrein gene (Klk1) had resulted in 24 paralogs in mouse. Here we demonstrate a different evolution of rat glandular kallikrein genes. Repeated duplications of an approximately 30-kb region, encompassing Klk1, Klk15, and Klk2-ps, resulted in 10 copies of each gene, but only the Klk1 paralogs are functional. The number of genes varies also between nonrodent mammals, e.g., there are probably no paralogs to KLK1 in cow and pig, whereas horse could have up to 5. In the dog, the gene encoding the prostatic arginine esterase was identified as an ortholog to the progenitor of the PSA and hK2 genes, and it carries the same conserved androgen-responsive elements directing prostate transcription as these genes. This is highly interesting with respect to animal models of benign prostate hyperplasia and prostate adenocarcinoma--diseases that have been described only in humans and dogs.